Post-Traumatic Stress Associated with Telework-Related Job Limitation in Latin America - Briceño, Mariluz (2023)
“During the pandemic, there has been evidence of work limitations during telework, which are believed to cause mental health problems. Our objective was to assess the association between perceived work limitations during telework and posttraumatic stress during the COVID-19 pandemic in Latin America. A cross-sectional study was conducted in Latin America in 2020. Exposure was measured by self-reporting using a self-perception questionnaire; the SPRINT-E questionnaire was used for outcome measurements. Generalized linear models were applied. Of 1329 participants, 15.2% (n = 202) had posttraumatic stress. In a multivariate analysis, the highest frequency of posttraumatic stress was found among those with moderate depression or more (PR = 1.29; 95% CI: 1.03–1.61), moderate or more anxiety (PR = 2.34; 95% CI: 1.61–3.41), and moderate or more stress (PR = 2.45; 95% CI: 1.46–4.12). In conclusion, there is an association between perceived work limitations during telework and posttraumatic stress in Latin American workers. For this reason, it is recommended that occupational physicians, companies, and institutions assess the frequency of posttraumatic stress and monitor the mental health of workers. “